2021
DOI: 10.1080/1750984x.2021.1929402
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the relationship between flow states and performance

Abstract: Flow is an optimal experience that has received particular interest within sport because of a possible relationship with enhanced athletic performances. Yet, the strength and direction of the putative flow-performance relationship remain unclear. Consequently, a PRISMA guided systematic review was conducted in May 2020 to examine the empirical evidence for a flowperformance relationship, to examine potential mechanisms, and to assess the quality of current evidence. Peer-reviewed articles that examined the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 77 publications
1
30
0
Order By: Relevance
“…A systematic review has also shown that there is a small to moderate relationship between FS and performance. The results show that such a relationship is consistent in both games and sports activities (Harris et al, 2021).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…A systematic review has also shown that there is a small to moderate relationship between FS and performance. The results show that such a relationship is consistent in both games and sports activities (Harris et al, 2021).…”
Section: Introductionsupporting
confidence: 65%
“…The pandemic situation complicated communication and collaboration with music institutions in order to take performance measures. But it would be especially interesting to take these measures since another issue that is not yet clear is whether the correlations between performance and FS are due to a good performance generating FS or a FS facilitating performance (Harris et al, 2021). However, this research would have to take on methodological challenges by inevitably posing causality hypotheses from an experimental approach.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since that time, the field of Positive Psychology has thrived, with thousands of studies on virtues, strengths, positive emotions, and positive communities and workplaces. We see this explosion of studies in reviews and meta-analyses on signature strengths and virtues (Schutte and Malouff, 2019 ), helping behavior (Lefevor et al, 2017 ), creativity (Acar et al, 2020 ), resilience (Liu et al, 2020 ), positive affect and broaden and build theory (Fredrickson, 2013 ), forgiveness (Wade et al, 2014 ), flow (Harris et al, 2021 ), gratitude (Boggiss et al, 2020 ), self-compassion (Wilson et al, 2019 ), passion (Pollack et al, 2020 ), mindfulness (Fjorback et al, 2011 ), hope (Griggs, 2017 ), optimism (Rozanski et al, 2019 ), meaning in life (Manco and Hamby, 2021 ), volunteering (Milbourn et al, 2018 ), positive forms of motivation (Ntoumanis et al, 2021 ), value affirmation (Howell, 2017 ), school-based positive interventions (Tejada-Gallardo et al, 2020 ), workplace positive interventions (Donaldson et al, 2019 ), and other forms of positive intervention (Carr et al, 2020 ). This research has led to a broadening of the definition of positive psychology itself, with theorists arguing that positive psychology needs to include both positive and negative constructs and needs to consider a wider number of methodologies and levels (e.g., group, culture, etc.…”
mentioning
confidence: 99%
“…Although enhanced performance has been identified as a consequent of flow, this characteristic would be difficult to assess in the present study because the comparisons were between activities, not between flow and non-flow within the context of the same activity. Perhaps reflecting the provisional nature of the flow construct, a subscale to assess enhanced performance is also absent from the FS2 (but see Harris et al 2021). Other potential consequents of flow, such as change in cognitive capacity or processing styles, have not received much empirical study .…”
Section: Rationale For Specific Itemsmentioning
confidence: 99%